Bardet–Biedl syndrome - Forsythe, Elizabeth (Nature Publishing Group, 2013)
Bardet–Biedl syndrome (BBS) is a rare autosomal recessive ciliopathy characterised by retinal dystrophy, obesity, post-axial polydactyly, renal dysfunction, learning difficulties and hypogonadism. Many associated minor features can be helpful in making a diagnosis and are important in the clinical management of BBS. The diagnosis is based on clinical findings and can be confirmed by sequencing of known disease-causing genes in 80% of patients. BBS genes encode proteins that localise to the cilia and basal body and are involved in cilia biogenesis and function. Mutations lead to defective cilia accounting in part for the pleiotropic effects observed in BBS. We provide an overview of BBS including the clinical findings, current understanding of cilia biology, and a practical approach to diagnosis, genetic counselling and up-to-date management.